2015
DOI: 10.20450/mjcce.2015.500
|View full text |Cite
|
Sign up to set email alerts
|

A validated high performance liquid chromatography method for determination of three bioactive compounds p-hydroxy benzoic acid, negundoside and agnuside in Vitex species

Abstract: A validated rapid and simple isocratic high performance liquid chromatography-photo diode array (HPLC-PDA) method was developed for identification and quantification of p-hydroxybenzoic acid and two iridoids (negundoside and agnuside) in the extracts of two Vitex species, Vitex negundo and Vitex trifolia. The separation of the three compounds was achieved on a RP-18 (250 mm × 4 mm, 5µm) column at 25 ºC using acetonitrile (15%) and 0.05% trifluoroacetic acid in water (85%). The limit of detection (LOD) were 1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Results showed that the lowest LOD of HA was 0.004 μg. The LOD and linearity range of HA were lower than those of reported methods [31, 32]. In addition, the linearity ranges and LODs of CA, MA, and SU were comparable or even lower than those of using HPLC–MS or colorimetric enzymatic methods [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the lowest LOD of HA was 0.004 μg. The LOD and linearity range of HA were lower than those of reported methods [31, 32]. In addition, the linearity ranges and LODs of CA, MA, and SU were comparable or even lower than those of using HPLC–MS or colorimetric enzymatic methods [33, 34].…”
Section: Resultsmentioning
confidence: 99%
“…Ten μL reaction mixture was injected at a flow rate of 1 mL/min at 25°C. Detection was carried out at 254 nm (Dhanani, Shah, Kumar, 2015).…”
Section: Synthesis and Characterization Of Platinum Derivativementioning
confidence: 99%
“…HPLC analysis was performed based on the previously published study (Dhanani, Shah, Kumar, 2015). As shown from Figure 2(C), there are two peaks in chromatogram at 3.5 minutes and 8.2 minutes, belonging to cis-4-hydroxyphenylplatinum(II)diamine 4-hydroxybenzoic acid, respectively.…”
Section: Synthesis and Characterization Of Cis-4hydroxyphenylplatinum...mentioning
confidence: 99%